Diversification strategy can reduce risk :A case study of Chinese commercial banks - Mo, Jingjie (2022)
Currently mainstream commercial banks will use diversification to reduce risk. However, there is still doubt that diversification can reduce business risk. Therefore, this paper will examine whether diversification can reduce the risk of commercial banks and whether human capital plays an intermediary role in it. In order to study the above issue, this paper analyses the financial data of 37 A-share listed commercial banks from 2011 to 2020, and the results show that diversification can reduce the risk of commercial banks, and human capital also plays a mediating effect of 5.56%.